Lingua receptiva or lingua franca? The choices of linguistic communication model on Polish-Czechborderland (based on the survey conducted in Hradec Králové Region and Kłodzko Land with Wałbrzych) - Nieporowski, Piotr Marcin; Steciąg, Magdalena; Zábranský, Lukáš (Instytut Języka Polskiego Polskiej Akademii Nauk, 2019)
The following article attempts to characterise an intercultural linguistic communication of people livingin the area of Polish-Czech borderland. The research conducted in 2018 aimed to determine the dominatingmodel of communication, as well as the reason behind its prevalence. The article contains the resultsof the analysis of linguistic competences of Poles and Czechs, completed with the portrayal of their languagepreferences. The models known as English as lingua franca, lingua receptiva, as well as their combinationconstitute a context of the considerations.
Keywords: borderland; communication; quantitative sociolinguistics; lingua receptiva; lingua franca